2013
DOI: 10.1111/tmi.12114
|View full text |Cite
|
Sign up to set email alerts
|

Task shifting an inpatient triage, assessment and treatment programme improves the quality of care for hospitalised Malawian children

Abstract: Objective We aimed to improve pediatric inpatient surveillance at a busy referral hospital in Malawi with 2 new programs: (1) the provision of vital sign equipment and implementation of an inpatient triage program (ITAT) that includes a simplified pediatric severity-of-illness score; (2) task-shifting ITAT to a new cadre of health care workers called “Vital Sign Assistants” (VSAs). Methods This study, conducted on the pediatric inpatient ward of a large referral hospital in Malawi, was divided into 3 phases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 32 publications
2
56
0
Order By: Relevance
“…Feedback was provided along with remediation if needed. Lay health workers, called vital sign assistants, were trained to ensure vital signs were recorded for each hospitalized patient [17]. Data entry was checked as a part of quality assurance protocols and the original paper forms were consulted as needed during data cleaning.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Feedback was provided along with remediation if needed. Lay health workers, called vital sign assistants, were trained to ensure vital signs were recorded for each hospitalized patient [17]. Data entry was checked as a part of quality assurance protocols and the original paper forms were consulted as needed during data cleaning.…”
Section: Methodsmentioning
confidence: 99%
“…Based on existing literature [6,13–17] and local clinical experience we selected the following variables a priori for investigation in the locally derived mortality prediction score: oxygen saturation, age-adjusted heart rate [19], malnutrition measured with mid-upper arm circumference (MUAC) and WHO weight-for-age z-score (WAZ), age, sex, presence of wheeze, unconsciousness, any danger sign, and vaccine status. Oxygen saturation, WAZ, MUAC and age were categorized as follows: SpO 2 as severe (<90%), moderate (90–92%) and normal (≥93%); WAZ as severe (<-3 SD), moderate (-3 to -2 SD) and normal (>-2 SD); MUAC as severe (<11.5 cm), moderate (11.5–13.5 cm) and normal nutrition (>13.5 cm); age as 2–11, 12–23 and 24–59 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous published PEWS tools which vary in accuracy predicting deterioration; 3,4 some have been successfully validated in multicenter trials, 5 and across various subspecialty populations. [7][8][9] PEWS are widely used in hospitals caring for pediatric oncology patients, 10 and one score has been validated to predict unplanned PICU transfer in hospitalized oncology and hematopoietic stem cell transplant (HSCT) patients. [7][8][9] PEWS are widely used in hospitals caring for pediatric oncology patients, 10 and one score has been validated to predict unplanned PICU transfer in hospitalized oncology and hematopoietic stem cell transplant (HSCT) patients.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of modified PEWS decreased the number of unplanned PICU transfers and improved PICU utilisation in Guatemala and assisted in identifying children with cancer who would benefit from more intensive monitoring in the intermediate care environment 30. A prospective nested case-controlled study in Malawi indicated that a locally developed PEWS could identify children at high risk of death 31. However, further analysis revealed that children who died were much more likely to have no PEWS or vital signs recorded at all.…”
Section: Where Are They Used and How Do They Perform?mentioning
confidence: 99%